2015
DOI: 10.1097/wtf.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Task sharing in rural Haiti

Abstract: Despite growing support for supervision after task sharing trainings in humanitarian settings, there is limited research on the experience of trainees in apprenticeship and other supervision approaches. Studying apprenticeships from trainees’ perspectives is crucial to refine supervision and enhance motivation for service implementation. The authors implemented a multi-stage, transcultural adaptation for a pilot task sharing training in Haiti entailing three phases: 1) literature review and qualitative researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…McLean et al . ( 2015 ) note that group training in the MHPSS sector often facilitates knowledge gain but is less effective in promoting skill building, even when role play and other participatory activities are included [also (e.g. Beidas & Kendall, 2010 ; Budosan, 2011 )].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McLean et al . ( 2015 ) note that group training in the MHPSS sector often facilitates knowledge gain but is less effective in promoting skill building, even when role play and other participatory activities are included [also (e.g. Beidas & Kendall, 2010 ; Budosan, 2011 )].…”
Section: Discussionmentioning
confidence: 99%
“…In emergencies and resource-poor settings across the world, non-specialists (people who lack prior professional or other specialised training in mental health and/or psychosocial support) are increasingly being trained to provide emotional and psychosocial support to people in distress (Mendenhall et al ., 2014 ; Haruf et al ., 2015 ; McLean et al ., 2015 ; O'Hanlon & Budosan, 2015 ; Singla et al ., 2017 ). These people may include community health volunteers, peer helpers, midwives, auxiliary health staff, teachers and those without a professional service role but who are active and respected within their communities, such as religious leaders and community leaders (McLean et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the burden of infectious disease and child and maternal health remain problematic in LMIC settings, no studies focused on the provision of ongoing training for non-communicable diseases (NCDs) and only one study focused on the provision of ongoing training for CHWs involved in mental healthcare. 51 NCDs have been described as the ‘social justice issue of our time’, 68 69 since they disproportionally affect populations in LMICs. 70 It is therefore imperative that more attention is directed towards providing ongoing training in the prevention and management of NCDs at a community level if we are to make realistic progress towards SDG 3.4, which has set the target of reducing premature mortality from NCDs by a third, by 2030.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, a community-based epidemiological study in the area documented a high degree of mental health needs, including depressive and anxiety symptoms and suicidal ideation [ 19 ]. At the same time, a brief mental health intervention by another NGO trained several community health workers to identify and provide support for mental health problems, as well as establishing a referral system to ZL [ 19 , 24 ]. The nearest mental health services were in the village of Cange, 28km away from the Kas’ market town.…”
Section: Methodsmentioning
confidence: 99%
“…One study found that 41% of patients presenting to a rural health clinic in 2010 complained of problems that may have been attributable to a mental disorder, but clinicians did not explore the psychosocial dimensions of the patients’ presenting problems in part due to insufficient access to mental health treatment [ 21 ]. Recognizing how few mental healthcare professionals worked in Haiti, several organizations implemented task-shifting mental healthcare initiatives using a range of models focusing on lay health workers in community-based settings [ 22 24 ], teachers in school-based settings [ 25 27 ], and primary care clinicians [ 28 ]. Starting in 2010, following a devastating earthquake, Zanmi Lasante (ZL), the Haitian affiliate of the international healthcare organization Partners In Health, developed a multi-tiered mental health program that included non-specialist mental health clinicians, community health workers (CHWs), and linkage to specialist mental healthcare located at 11 ZL-operated hospitals and primary care clinics [ 29 32 ].…”
Section: Introductionmentioning
confidence: 99%